Optical solitons and other solutions for coupled system of nonlinear Schrödinger’s equation with parabolic nonlocal law of refractive index by using the improved modified extended tanh function method - Samir, Islam; Badra, Niveen; Ahmed, Hamdy M.; Arnous, Ahmed H. (Optik (Stuttgart), 2022)
In this paper, the improved modified extended tanh function method is applied to secure optical soliton solutions in magneto-optic waveguides for coupled system of non-linear Schrödinger equation with parabolic non-local law of refractive index. Bright soliton solutions, dark soliton solutions and singular soliton solutions are obtained. Moreover, for the physical illustration of the obtained solutions, 3D and their corresponding 2D graph are presented.